Functional and radiological evaluations of high-energy tibial plateau fractures treated with doublebuttress plate fixation - Yu Z; Zheng L; Zhang Y; Li J; Ma B (European Journal of Medical Research, 2009)
Abstract Objective This study was designed to evaluate the functional and radiological outcomes of patients with complex tibial plateau fractures treated with double-buttress plate fixation. Methods Sixty five cases of complex (Schatzker type V and VI) tibial plateau fractures were treated with double-buttress plate fixation in our centre from September 2001 to September 2006 through two separate plate incisions. Fifty four patients were followed up for a period ranging from 12 to 48 months and evaluated for the functional and radiological outcomes by a series of standard questionnaire and measurement. Results Due to the good exposure without any extensive soft-tissue dissection of the double-buttress plate fixation, the fractures in all 54 patients were healed and the treatment achieved greater than 90% of satisfactory-to-excellent rates of reduction. The mean time of bone union was 15.4 weeks (range, 12-30 weeks), and the mean time of full weight-bearing was 18.7 weeks (range, 14-26 weeks). At the final follow-up visit, no patients showed knee instability; the mean range of motion was 107.6° (range, 85°-130°). For all patients, no statistically significant difference in the functional outcomes was observed between their 6-months and final follow-up visits; or in the radiological findings between their immediate postoperative and final follow-up examinations. Conclusion Double-buttress plate fixation is a feasible treatment option for bilcondylar and complex tibial plateau fractures. Although technically demanding, it offers reliable stability without additional postoperative adjuvant external fixation, and at the same time avoids extensive soft tissue dissection, allowing the early painless range of motion.